The mast cell: A Janus in kidney transplants - van der Elst, G.; Varol, H.; Hermans, M.; Baan, C. C.; Duong-van Huyen, J. P.; Hesselink, D. A.; Kramann, R.; Rabant, M.; Reinders, M. E. J.; von der Thüsen, J. H.; van den Bosch, T. P. P.; Clahsen-van Groningen, M. C. (Frontiers in Immunology, 2023)
Mast cells (MCs) are innate immune cells with a versatile set of functionalities, enabling them to orchestrate immune responses in various ways. Aside from their known role in allergy, they also partake in both allograft tolerance and rejection through interaction with regulatory T cells, effector T cells, B cells and degranulation of cytokines and other mediators. MC mediators have both pro- and anti-inflammatory actions, but overall lean towards pro-fibrotic pathways. Paradoxically, they are also seen as having potential protective effects in tissue remodelling post-injury. This manuscript elaborates on current knowledge of the functional diversity of mast cells in kidney transplants, combining theory and practice into a MC model stipulating both protective and harmful capabilities in the kidney transplant setting.